Students’ perception of English as a medium of instruction (EMI) in English classroom - Denni Rahmadani (Journal on English as a Foreign Language, 2016)
This study aims to uncover what extent of the students’ expectation of English as a medium of instruction (EMI) used by the English teacher in teaching English at senior high schools in Palangka Raya, Indonesia. A survey research method was applied. The survey was conducted at the four schools: MAN Model, MA Muslimat NU, SMAN 4, and SMKN 2 in Palangka Raya. To collect the data, the study employs the questionnaire with 10 items given to 134 students of the second grade taken from one class of each of the schools. It was used the cluster random sampling technique to take the samples. The items were designed for evaluating the factual, behavioral, and attitudinal condition of EMI in the English classroom. As a result of the study, it is shown that most of the students agree of EMI dominantly applied by the English teacher in the teaching of English subject. By implementing EMI in this classroom, it can increase students’ English ability with appropriate English standard, motivate them to learn English, improve their confidence to speak English, help them to comprehend English textbook or article, and assist them to understand the international culture.